2016
DOI: 10.1159/000449380
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Peritonitis: Correlation of Antenatal Diagnosis and Postnatal Outcome - An Institutional Experience over 10 Years

Abstract: Objective: To identify the fetal and neonatal imaging characteristics of meconium peritonitis (MP) and their clinical outcome. We also studied the role of prenatal ultrasound (US) in antenatal diagnosis and its use in predicting the need for surgical intervention postnatally. Material and Methods: We conducted a retrospective analysis of a cohort of 18 infants with MP from April 2004 to March 2014. Results: Prenatal US detected MP-related abnormalities in 15/18 (83.3%) fetuses. The median gestational age at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
3
25
0
3
Order By: Relevance
“…In another study, Ping et al (n = 18) reported that the presence of a meconium pseudocyst was associated with the need for surgery and poor outcome. However, in their study, the prenatal ultrasound DR of fetal pseudocyst was only16.7%, and the remainder were confirmed histologically only after neonatal surgery . In our cohort, we only had six cases (12.2%) who presented with a pseudocyst on antenatal ultrasound.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In another study, Ping et al (n = 18) reported that the presence of a meconium pseudocyst was associated with the need for surgery and poor outcome. However, in their study, the prenatal ultrasound DR of fetal pseudocyst was only16.7%, and the remainder were confirmed histologically only after neonatal surgery . In our cohort, we only had six cases (12.2%) who presented with a pseudocyst on antenatal ultrasound.…”
Section: Discussionmentioning
confidence: 83%
“…However, in their study, the prenatal ultrasound DR of fetal pseudocyst was only16.7%, and the remainder were confirmed histologically only after neonatal surgery. 21 In our cohort, we only had six cases (12.2%) who presented with a pseudocyst on antenatal ultrasound. Interestingly, the incidence of pseudocyst in the surgical group was lower compared with the nonsurgical group, but this did not reach statistical significance.…”
Section: Independent Predictors Of Poor Outcomementioning
confidence: 99%
“…After title and abstract screening, 56 studies were selected for full-text analysis. Fourteen manuscripts met the inclusion criteria and were included for data analysis [2,7,[12][13][14][15][16][19][20][21][22][23][24]. The addition of our institutional findings resulted in a total of 15 studies.…”
Section: Results From Meta-analysismentioning
confidence: 99%
“…In 2 Drittel der Fälle (66,5 %) war eine postnatale abdominale Operation erforderlich. Der stärkste Prädiktor für die neonatale Chirurgie war eine Mekonium-Pseudozyste (OR 6,75; 95 %-KI 2,53-18,01), gefolgt von Darmdilatation (OR 4,17; 95 %-KI 1,93-9,05) und Aszites (OR 2,57; 95 %- KI 1,24). Die häufigste Ursache für Darmperforation und Mekoniumperitonitis, die in 52,2 % der Fälle gefunden wurde, war die Dünndarmatresie.…”
Section: Conclusion Meconium Pseudocysts Bowel Dilation Andunclassified
See 1 more Smart Citation